2004
DOI: 10.1103/physrevb.70.235408
|View full text |Cite
|
Sign up to set email alerts
|

Doping and planar defects in the formation of single-crystal ZnO nanorings

Abstract: We have recently reported the growth of freestanding, single-crystal, seamless nanorings of zinc oxide via a spontaneous self-coiling process during the growth of polar-nanobelts [X.Y. Kong et al., Science 303, 1348(2004]. The nanoring is made by coaxial and uniradius loop-by-loop winding of a fine ZnO nanobelt. An important fact is that each and every nanoring is made of a nanobelt that contains basal-plane planar defects, which are suggested to be important for leading the fastest growth of the nanobelt as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 27 publications
6
73
2
Order By: Relevance
“…HRTEM and selected-area electron diffraction (SAED) recorded from the side-lying nanobelt further reveal the existence of the stacking faults along the c axis. The switched growth direction from [0001] to , the existence of large polar surfaces, and the stacking faults are in good agreement with the previous reports [21,27] on Indoped ZnO nanobelts; therefore, the switch in direction here and the stacking fault formation during the growth www.eurjic.orgshould also be attributed to the structural modulation induced by In doping. It is worth mentioning that in most previous studies, successful doping will usually be accompanied by the degradation of the alignment/symmetry for a nanostructure array; in contrast, here, not only is successful In doping achieved for the ZnO nanobelts but also the alignment and in-plane symmetry is well preserved.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…HRTEM and selected-area electron diffraction (SAED) recorded from the side-lying nanobelt further reveal the existence of the stacking faults along the c axis. The switched growth direction from [0001] to , the existence of large polar surfaces, and the stacking faults are in good agreement with the previous reports [21,27] on Indoped ZnO nanobelts; therefore, the switch in direction here and the stacking fault formation during the growth www.eurjic.orgshould also be attributed to the structural modulation induced by In doping. It is worth mentioning that in most previous studies, successful doping will usually be accompanied by the degradation of the alignment/symmetry for a nanostructure array; in contrast, here, not only is successful In doping achieved for the ZnO nanobelts but also the alignment and in-plane symmetry is well preserved.…”
Section: Resultssupporting
confidence: 85%
“…Taking In-doped ZnO 1D nanostructures as an example, it has been found that the growth direction and the morphology of the nanostructures can be dramatically changed due to In doping. [20][21][22][23] However, nanodevice applications require not only the doping and the superlattice realizations for these 1D nanostructures but also the good order and high quality of the selfassembly (which is crucial for the integration); clearly, the current approaches based on self-assembly cannot meet this criterion and more efforts are therefore urgently needed. Furthermore, few efforts have been made to improve the quality of hierarchical 1D nanostructure assembly [24,25] despite its importance in building bottom-up, self-assembled 1D nanomaterial circuits.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of NH 3 above which the nanostructure may be formed in hydrothermal ZnO synthesis. In this study, the growth of ZnO nanorods in zinc sulfate solution was observed from a solution pH of 10.3.…”
Section: Role Of Oh − Concentration In the Synthesis Of Zno Nanorodsmentioning
confidence: 99%
“…11,12 Quantitative analysis of the nanorings showed the atomic ratio In:Zn of about 1:15 suggesting In incorporation into the ZnO lattice, instead of the formation of the compound Zn 4 In 2 O 7 observed in the nanobelts of this work. The formation of nanorings by rolling up of nanobelts is explained 13 by a reduced overall dipole moment, and hence a reduction in electrostatic energy, in a circular ring.…”
mentioning
confidence: 99%